(G,ϕ) -crossed product on (G,ϕ)-quasiassociative algebras - Mamede Albuquerque, H.M.; Félix Barreiro, M.E.; Sánchez Delgado, J.M. (Algebra and Discrete Mathematics, 2017)
The notions of (G,ϕ)-crossed product and quasicrossed system are introduced in the setting of (G,ϕ)-quasiassociative algebras, i.e., algebras endowed with a grading by a group G, satisfying a ``quasiassociative'' law. It is presented two equivalence relations, one for quasicrossed systems and another for (G,ϕ)-crossed products. Also the notion of graded-bimodule in order to study simple (G,ϕ)-crossed products is studied.